2022
DOI: 10.1111/srt.13221
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing deep learning for dermal matrix quality assessment on in vivo line‐field confocal optical coherence tomography images

Abstract: Background Line‐field confocal optical coherence tomography (LC‐OCT) is an imaging technique providing non‐invasive “optical biopsies” with an isotropic spatial resolution of ∼1  μm and deep penetration until the dermis. Analysis of obtained images is classically performed by experts, thus requiring long and fastidious training and giving operator‐dependent results. In this study, the objective was to develop a new automated method to score the quality of the dermal matrix precisely, quickly, and directly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Future studies evaluating the application of this method in scarring alopecia could be conducted. 11 LC-OCT appears to be an excellent diagnostic tool for in vivo examination of inflammatory skin diseases. As the preliminary study has shown, LC-OCT appears to be a rapid and effective tool that can help distinguish between lichenoid papular diseases and their clinical simu-lators in patients during childhood and adolescence.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Future studies evaluating the application of this method in scarring alopecia could be conducted. 11 LC-OCT appears to be an excellent diagnostic tool for in vivo examination of inflammatory skin diseases. As the preliminary study has shown, LC-OCT appears to be a rapid and effective tool that can help distinguish between lichenoid papular diseases and their clinical simu-lators in patients during childhood and adolescence.…”
Section: F I G U R Ementioning
confidence: 99%
“…Future studies evaluating the application of this method in scarring alopecia could be conducted. 11 …”
Section: Figurementioning
confidence: 99%